POD NUMBER AND PHOTOSYNTHESIS AS PHYSIOLOGICAL SELECTION CRITERIA IN SOYBEAN (Glycine max L. Merrill) BREEDING FOR HIGH YIELD - Sitompul, S.M.; Sari, Dian Indra; Krisnawati, Erna; Mulia, Rachmad Harri; Taufiq, M. (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2015)
Field studies were conducted in two years using 638 F2 and 1185 F3 lines of selected 16 F1 and 15 F2 parent lines (³80 pods plant-1) to evaluate pod number and CO2 exchange rate (CER) as selection criteria. Pod and seed number, and seed weight of individual lines were observed during harvesting time, and CER of randomly selected 32 F2 and 30 F3 lines was measured at initial seed filling stage. The selection of F2 lines based on pod number to generate F3 lines increased the average of seed yield by 39%, and pod number by 77% in F3 lines compared with F2 lines. A close relationships was found between seed weight and pod or seed number per plant. Net CER responded sensitively to a reduction of light in a short-term and showed 78% of F2 lines and all F3 lines with maximum CER (Pmax)³20 mmolCO2.m-2.s-1. The ratio of pod number per plant and Pmax varied between lines and were used to group lines resulting in close relationships between Pmax and pod number. It is concluded that the use of pod number and CER (Pmax) as selection criteria offers an alternative approach in soybean breeding for high yield. Keywords: CO2 exchange rate (CER), Glycine max L. Merrill, model, pod number, soybean